Prostaglandin F2α for lactating dairy cows with silent estrus - S.S. Plunkett; Jeffrey S. Stevenson; Edward P. Call (Kansas Agricultural Experiment Station Research Reports, 1984)
Two experiments were conducted in 17 dairy herds in NE Kansas to determine the effectiveness of prostaglandin F2α(PGF) for reducing intervals to conception for cows with silent or unobserved estrus. Cows that failed to be seen in heat so they could be inseminated after calving (Exp. 1) and cows that did not return to estrus after AI and were not pregnant when presented to veterinarian for pregnancy examination (Exp. 2) were assigned alternately to be given PGF or to receive no treatment after detection of a palpable corpus luteum. Cows were inseminated at 72 and 96 hr after PGF treatment if not detected in heat. Intervals from treatment to conception were reduced after PGF treatment. Cows with unobserved estrus can be inseminated sooner and have shorter intervals to conception if PGF is used for reproductive management in association with a routine herd health program.; Dairy Day, 1984, Kansas State University, Manhattan, KS, 1984;
Keywords: Kansas Agricultural Experiment Station contribution; no. 85-116-S; Report of progress (Kansas Agricultural Experiment Station); 460; Dairy; Prostaglandin F2-α; Estrus; Artificial Insemination (AI)